Co-assembled Supramolecular Nanofibers With Tunable Surface Properties for Efficient Vaccine Delivery - Wang, Zhongyan; Ren, Chunhua; Shang, Yuna; Yang, Cuihong; Guo, Qingxiang; Chu, Liping; Liu, Jianfeng (Frontiers in Chemistry, 2020)
The utilization of nanotechnology to deliver vaccines and modulate immunity has shown great potential in cancer therapy. Peptide-based supramolecular hydrogels as novel vaccine adjuvants have been found to effectively improve the immune response and tumor curative effect. In this study, we designed a set of reduction-responsive self-assembled peptide precursors (Fbp-GDFDFDYD(E, S, or K)-ss-ERGD), which can be reduced by glutathione (GSH) into Fbp-GDFDFDYD(E, S or K)-SH for forming of hydrogel with different surface properties (E-gel, S-gel, and K-gel, respectively). Using the same method, co-assembled hydrogel vaccines (E-vac, S-vac, and K-vac, respectively) can also be prepared by mixing different precursors with antigens before GSH reduction. Through TEM observation of the nanostructure, we found that all the co-assembled hydrogels, especially K-vac, possessed much denser and more unified nanofiber networks as compared with antigen-free hydrogels, which were very suitable for antigen storage and vaccine delivery. Although the three peptides adopted similar β-sheet secondary structures, the mechanical properties of their resulted co-assembled hydrogel vaccines were obviously different. Compared to E-vac, S-vac had a much weaker mechanical property, while K-vac had a much higher. In vivo experiments, co-assembled hydrogel vaccines, especially K-vac, also promoted antibody production and anti-tumor immune responses more significantly than the other two vaccines. Our results demonstrated that co-assembled hydrogels formed by peptides and antigens co-assembly could act as effective vaccine delivery systems for boosting antibody production, and different immune effects can be acquired by tuning the surface properties of the involved self-assembling peptides.